Science project ideas about trees - Gardner, Robert, 1929-; Katari, Jacob (Berkeley Heights, NJ : Enslow, 1997)
Contains many experiments introducing the processes that take place in plants and trees.
Includes bibliographical references (p. 94) and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
5.9.
5.9
Keywords: Botany projects -- Juvenile literature; Trees -- Juvenile literature; Trees -- Experiments -- Juvenile literature; Experiments; Science projects; Trees; Trees -- Experiments; Experiments; Science projects; Trees; Trees -- Experiments